2016
DOI: 10.4103/0976-237x.194106
|View full text |Cite
|
Sign up to set email alerts
|

A study of Ki-67 expression and its clinicopathological determinants in nondysplastic oral leukoplakia

Abstract: Context:Oral cancer is the third most prevalent malignancy in India. Leukoplakia is its most common precursor lesion.Aims:This study aimed at evaluation of the Ki-67 expression and thereby detection of the dysplastic potential in histopathologically nondysplastic oral leukoplakia (OL). Secondarily, another purpose was to correlate various clinicopathological factors with the labeling indices (LIs) of Ki-67 in those cases as well.Settings and Design:In total, 97 OL cases were examined. Relevant clinical and dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The mean value of LI was found to increase as the nature of the lesion changed especially from dysplasia to SCC. In the present study, normal oral epithelium expressed the lowest Ki-67 LI while the proliferative activity of non dyplastic leukoplakia was higher, similar to Mondal et al [20] however this was contrary to, Dwivedi et al [21] and Kumar et al [22] who noticed very little disagreement between the mean LIs of normal oral epithelium (13.65%) and nondysplastic OL (12.78%). In our study, the discrepant and relatively higher mean LIs within leukoplakia lacking any dysplasia are ~ 361 ~ possibly a consequence of smaller sample sizes.…”
Section: Discussionsupporting
confidence: 58%
“…The mean value of LI was found to increase as the nature of the lesion changed especially from dysplasia to SCC. In the present study, normal oral epithelium expressed the lowest Ki-67 LI while the proliferative activity of non dyplastic leukoplakia was higher, similar to Mondal et al [20] however this was contrary to, Dwivedi et al [21] and Kumar et al [22] who noticed very little disagreement between the mean LIs of normal oral epithelium (13.65%) and nondysplastic OL (12.78%). In our study, the discrepant and relatively higher mean LIs within leukoplakia lacking any dysplasia are ~ 361 ~ possibly a consequence of smaller sample sizes.…”
Section: Discussionsupporting
confidence: 58%
“…Ki-67 positivity was assessed using a scoring system proposed by Kannan. 22,23,24 The details of scoring interpretation are as follows: Score 0 = 0 -5% Score 2 = 6-25% Score 4 = 26 -60% Score 6 = 61 -99% 22 Statistical analysis was carried out using Statistical Package for Social Sciences version 19. Frequency and percentages were calculated for categorical variables, i.e., level of expression of Ki-67 in basal, parabasal and suprabasal layers of epithelium.…”
Section: Methodsmentioning
confidence: 99%
“…Several authors tried to correlate hyperkeratosis with OL but they did not associate it with the use of snuff. 24,26,30,31 Similarly. international literature regarding immunohistochemical expression of Ki-67 in snuff users in basal, parabasal and suprabasal layers for comparison with this study could not be found on extensive search.…”
Section: Ki-67 Positivity (Score) Basal Layer N(%) Parabasal Layer N(mentioning
confidence: 99%
“…Although the significant roles played by oncogenes and tumor suppressor genes in the development of OSCC have been explored, there are few data on the pathogenesis of OSMF as well as of its MT at the molecular level. [ 8 , 9 ] Therefore, the early detection of potentially malignant OSMF has been crucial in the inhibition of oral cancer. Thus the present study aims to evaluate the demographic (age, education, and socioeconomic status) and pathological factors (habits with duration and frequency) for OSMF and degree and pattern of expression of p53 in OSMF, OSCC, and normal patients and to study the correlation between p53 expression with clinical staging and histological grading of OSMF.…”
Section: Introductionmentioning
confidence: 99%